The Face of War - Gellhorn, Martha (London Rupert Hart-Davis, 1959)
Martha Gellhorn was a war correspondent for nearly fifty years. From the Spanish Civil War in 1937 through the wars in Central America in the mid-eighties, her reports reflected her feelings for people no matter what their political ideologies, and the openness and vulnerability of her conscience. "I wrote very fast, as I had to," she says, "afraid that I would forget the exact sound, smell, words, gestures, which were special to this moment and this place." Whether in Java, Finland, the Middle East, or Vietnam, she used the same approach.
Keywords: Military history, Modern -- War -- History, Modern -- War correspondents -- United States